Utilization of Local Plant: Beluntas Leaves (Pluchea indica Leaves) to Enhance Breast Milk Production - Iin Prima Fitriah; Mardiani Bebasari; Bunga Meilizayosa; Athifa Zuharani; Salsabila Febriwandi (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background of study: Breast milk plays a crucial role in infant growth and maternal health; however, some mothers experience insufficient production due to physiological, psychological, and nutritional factors. A promising alternative to address this issue is the use of local plants with galactagogue properties, which stimulate milk production. Methods: This community service activity aimed to support breastfeeding mothers through health education with a counseling method on the importance of breastfeeding, an explanation of the benefits of beluntas leaves (Pluchea indica), and a demonstration of their preparation by boiling. Result: The results of this activity show that the majority of the 84 respondents (91.67%) felt the benefits of the counseling and demonstration on processing beluntas leaves. Evaluation results indicated that participants showed improved understanding of breastfeeding benefits and expressed interest in trying beluntas consumption at home as a natural method to increase milk supply. The integration of health education, scientific explanation, and practical demonstration effectively enhanced both knowledge and motivation among mothers. Conclusion: Therefore, the utilization of beluntas leaves has the potential to serve as a simple, applicable, and community-based intervention to promote increased breast milk production.